Effectiveness Of Utilizing Productive Zakat In Increasing The Income Of Mustahik Micro Businesses at BAZNAS Temanggung Regency In 2023. - Lucky Fitria Ningsih; Titik Hinawati; Ainun Khabib; Mila Fursiana Salma Musfiroh (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
This research aims to determine the effectiveness of utilizing productive zakat in increasing the income of mustahik micro businesses at BAZNAS Temanggung Regency in 2023. This research focuses on the effectiveness and strategies used by BAZNAS Temanggung in utilizing productive zakat to increase income. The research uses a qualitative descriptive method with a phenomenological approach, meaning that this approach is focused on exploring, understanding and interpreting the meaning of phenomena, events and their relationships with ordinary people in certain situations. The data collection technique in this research uses interview and documentation methods. After the data is collected, the author uses Sugiyono's analysis techniques such as data reduction, presenting data, drawing conclusions for data analysis. The results of this research show that the use of productive zakat in increasing the income of mustahik micro businesses in BAZNAS Temanggung Regency has been effective and has had a positive impact on the mustahik in the sample. This is due to increased sales turnover, which can increase the profits of the mustahik. Keywords: Effectiveness, Utilization Productive Zakat, Increasing Mustahik Income, Micro Businesses